Strategi Corporate Branding Dalam Meningkatkan Brand Equity Pada Konsumen PT. Distribusi Sukses Mandiri - Alif Dava Mahesa; Arfian Suryasuciramdhan; Istialdi Pratama Haris; Lika Mulki Latief; Ninda Ela Putri; Yusep Irsyad Najib Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the corporate branding strategy implemented by PT Distribusi Sukses Mandiri and its impact on increasing brand equity among consumers. This study aims to identify the key elements of the company's corporate branding strategy, evaluate its effectiveness in building positive perceptions and consumer loyalty. The results showed a positive and significant influence between the corporate branding strategy implemented by PT Distribusi Sukses Mandiri on consumer brand equity. This research provides a practical contribution for PT Distribusi Sukses Mandiri in improving its corporate branding strategy and provides theoretical implications for the development of corporate branding and brand equity studies in Indonesia.